2019
DOI: 10.1177/1466138119892017
|View full text |Cite
|
Sign up to set email alerts
|

Welfare, social citizenship, and the spectre of inequality in Amsterdam

Abstract: This article explores how notions of citizenship are negotiated in encounters between parents and youth care professionals in Amsterdam in the context of heated debates over citizenship and belonging. We draw on ethnographic research on Egyptian migrant parents’ interactions with the welfare state, and on the work of youth care professionals. We found that both parents and professionals were invested in universal forms of citizenship. Parents wanted to be treated like their fellow citizens regardless of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The studies that do exist point to a second implementation paradox inherent to diversity-mainstreaming policies: the vagueness of 'diversity' can inhibit concrete action to address inequalities linked to ethnicity and race. For example, Nieswand (2017) and De Koning and Ruijtenberg (2019) found that diversity-mainstreaming led to a 'colour-blinding' of care provision. As frontline workers attempted 'not to see colour', aspects of cultural and ethnic difference became unspeakable in conversations with and about families receiving care.…”
Section: Diversity-mainstreaming Policies Through a Crafting Lensmentioning
confidence: 99%
“…The studies that do exist point to a second implementation paradox inherent to diversity-mainstreaming policies: the vagueness of 'diversity' can inhibit concrete action to address inequalities linked to ethnicity and race. For example, Nieswand (2017) and De Koning and Ruijtenberg (2019) found that diversity-mainstreaming led to a 'colour-blinding' of care provision. As frontline workers attempted 'not to see colour', aspects of cultural and ethnic difference became unspeakable in conversations with and about families receiving care.…”
Section: Diversity-mainstreaming Policies Through a Crafting Lensmentioning
confidence: 99%
“…In welfare encounters in the social domain, we see an emphasis on equality, for instance in the forms of universalist or generic approaches, and the professional ethics that derive from such approaches. and support families (De Koning and Ruijtenberg, 2022;Johansen, 2022).…”
Section: The Universal and Differencementioning
confidence: 99%
“…In her analysis of parenting encounters between Palestinian parents and welfare workers in Denmark, Johansen argues that the potential of punitive action and harm entwines with immigrant parents' prolonged experiences of crisis and determines their ways of seeing and being as parents, including how they relate to people in their closest social and institutional surroundings. Such in the Amsterdam case (De Koning and Ruijtenberg, 2022), delinquency in the Aarhus case (Johansen, 2022), or the so-called communautarist identifications and socialities in Paris (Vollebergh, 2022). Such tropes function as icons of troublesome difference in these contexts.…”
Section: The Universal and Differencementioning
confidence: 99%
See 2 more Smart Citations